Demographic proles of epileptic patients and their awareness towards epilepsy with the inuence on compliance - Mian, Md Ferdous; Jobayer, Mohammad; Afroz, Zeenat; Chowdhury, Ahmed Hossain; Chowdhury, Rajib Nayan; Habib, Mansur; Mohammad, Quazi Deen (Bangladesh Medical Journal, 2016)
There are about 2 million epilepsy patients in Bangladesh. The aim of this study was to correlate the demographic parameter of epilepsy patients with their knowledge about the disease and also with the compliance of antiepileptic drugs. This retrospective study was carried out in the Department of Neurology at Dhaka Medical College Hospital, Bangladesh from July 2010 to June 2012. A total of 100 epilepsy patients of any age and sex attending the epilepsy clinic were enrolled of which 50 patients who had experienced one or more seizures over last six months were designated as uncontrolled epileptic patients were in case group and 50 patients who were seizure-free for six months were designated as controlled epileptic patients were in control group. Mean age of case and control groups were 21.84 ±8.70 and 23.94 ±10.28 years respectively. Most of the epilepsy patients were between the age of 11 to 30 years that was 88% in case group and 76% in control group. Male was predominant than female in both group. Among study population 70% and 58% had educational status below Primary level in case and control group respectively. Seventy percent of uncontrolled epilepsy patients were from low income group and 62% of them were unemployed. Maximum (68% in case and 44% in control group) patients were from rural area. Almost all controlled epilepsy patients took drugs regularly, whereas 52% patients with uncontrolled epilepsy did not took drugs regularly and 64% of them had history of missing anti-epileptic drugs. Knowledge about the disease, treatment and prognosis of epilepsy was better in control group than in case group of epilepsy patients. It may be concluded that lower socioeconomical condition, less education and lack of awareness about epilepsy and non-affordability, limited availability of drugs, lack of counseling have contributed to the non-compliance of antiepileptic drugs. Bangladesh Med J. 2016 Jan; 45 (1): 20-24